FASHION IN UKRAINIAN WOMEN’S PRESS OF NORTH AMERICA IN THE 50’S – 60’S: THE PHENOMENON OF "EMBROIDERY PARTIES" - ЦИМБАЛА, Л. І. (Art and Design, 2023)
Purpose of the scientific research is related to the features of fashion trends and the translation of ethnic traditions in the publications of leading women’s magazines in North America during the 50s and 60s., correlation of diaspora women’s fashion with the ethno-fashion in Soviet Ukraine and world fashion trends especially. Methodology of the research has been based on the historical, analytical methods. The method of retrospective description and comparative analysis is use in case to identify the peculiarities of the phenomenon of "embroidery parties" within the women’s culture of the Ukrainian diaspora in North America and precisely due to its distribution through women’s magazines. Results of the study trace the chronology of popularization of the phenomenon of "embroidery parties" in the Ukrainian communities of North America in the 50s and 60s., the evolution of ethnic fashion and the style of women’s clothing ensembles, published in the women’s press, the causes and consequences of the phenomenon in the Ukrainian diaspora’s fashion and its identification in the local and all-Ukrainian context. Women’s magazines, which began their activities in women’s political and social centers of North America in the post-war period ("Women’s World", "Woman in the World", "Our Life", "Promin"), in addition to continuing the "nurturing traditions of Ukrainian culture", became an important platform for the spread of new fashion trends and popularization of Ukrainian ethno-fashion, contributed to the the phenomenon of "embroidery parties " (fashion shows) within the Ukrainian women’s organizations. For the first time, the study reveals the embroidery parties, popularized in the women’s magazines of North America in the 50–60-s as a phenomenon, unique to North American culture, but creative to all Ukrainian Ethnic Fashion discourse. Practical significance of research lies in the possibilities of using the results in the comprehensive vision of Ukrainian ethnic fashion of the post-war period both in the diaspora and in Soviet Ukraine, the continuity of broadcasts of traditional Ukrainian Art in modern Ukrainian design.